2019
DOI: 10.3390/md17030184
|View full text |Cite
|
Sign up to set email alerts
|

Brevenal, a Marine Natural Product, is Anti-Inflammatory and an Immunomodulator of Macrophage and Lung Epithelial Cells

Abstract: Chronic respiratory diseases, including chronic obstructive pulmonary disease (COPD), cystic fibrosis, and asthma, are some of the leading causes of illness and fatalities worldwide. The search for novel treatments led to the exploration of marine natural products as drug candidates to combat the debilitating effects of mucus accumulation and chronic inflammation. Previous research showed that an alga-derived compound, brevenal, could attenuate the effects of inflammatory agents, but the mechanisms by which it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…This functional response is in agreement with the flow cytometry data (Figure 4), where compound 3 had the most effects on macrophage expression of activation markers and size/complexity. Compound 3 resulted in an approximately 22% decrease in TNFα secretion, which is similar to what has been found from brevenal, another natural product, derived from Karenia brevis [35].…”
Section: Introductionsupporting
confidence: 77%
“…This functional response is in agreement with the flow cytometry data (Figure 4), where compound 3 had the most effects on macrophage expression of activation markers and size/complexity. Compound 3 resulted in an approximately 22% decrease in TNFα secretion, which is similar to what has been found from brevenal, another natural product, derived from Karenia brevis [35].…”
Section: Introductionsupporting
confidence: 77%
“…In fact a phase IIa clinical trial to evaluate safety and efficacy of subcutanous administration of anakinra in patients with cystic fibrosis is in progress (EudraCT Number: 2016-004786-80). It is notable that inhibition of TLR4 signalling was the most effective means of blocking NLRP3 activation in our study, which suggests that targeting this pathway may be a therapeutic option in CF (Keeler et al, 2019; Greene et al, 2008). These novel data, along with our observation that decreased intracellular K + levels upon stimulation with ATP in cells with CF-associated mutations, correlates with the characteristic and excessive ENaC-mediated Na + transport, suggest that CF-associated mutations lower the threshold for NLRP3 assembly, rather than priming this key intracellular component of innate immune defenses.…”
Section: Discussionmentioning
confidence: 60%
“…In 2005, studies in cellular and animal models of cystic fibrosis, which affects more than 70 000 people worldwide, revealed brevenal to be therapeutically active at nanomolar to picomolar concentrations, and in 2018, the US Food and Drug Administration approved brevenal as an orphan drug for the treatment of this disease. Recent studies have also shown that brevenal has anti‐inflammatory properties and may be useful for treating other chronic respiratory diseases . However, producing a brevenal‐derived drug would be very expensive because the currently available methods for MLP synthesis are laborious .…”
Section: Methodsmentioning
confidence: 99%